Relationship between Polymorphism of Angiotensin Converting Enzyme Gene with Symptoms of Depression in Schizophrenic Patients - Nuralita, Nanda Sari; Thristy, Isra; Lubis, Debby Mirani (Buletin Farmatera, 2022)
In schizophrenic patients, symptoms of depression are often found which can lead to adverse effects on the treatment process, such as increasing the length of treatment, increasing the possibility of relapse, non-adherence in taking medication, and can also lead to suicide in schizophrenic patients. In schizophrenic patients, the activity of the central angiotensin converting enzyme (ACE) gene is altered and angiotensin II interacts with central dopamine, thereby contributing to the pathophysiology of schizophrenia. In addition, it is likely that the ACE gene variant is also involved in the development of depressive symptoms in schizophrenic patients. This research is a categorical analytic study with a cross sectional method, the sampling method is non-probability sampling with consecutive sampling type, with a total sample of 42 people. There was no significant difference between depression symptoms and ACE gene polymorphisms with P value = 0.746. There was no significant difference between depression symptoms and ACE gene polymorphisms.